2011
DOI: 10.3138/ptc.2009-41
|View full text |Cite
|
Sign up to set email alerts
|

Inter-professional Education in the Acute-Care Setting: The Clinical Instructor's Point of View

Abstract: Purpose: The purpose of this study was to gain an understanding of the opportunities and challenges involved in providing clinical inter-professional education (IPE) to physical therapy (PT) students in the acute-care setting from the perspective of PT clinical instructors (CIs). Methods: Focus groups were conducted in four acute-care hospitals in Toronto. Participants were recruited using a purposive and convenience sampling approach in order to enhance our understanding of the perceptions of acute-care PT CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…An excellent example would be the development of a model of inter-professional education that could enhance care through better collaboration across health disciplines in health care settings. [30][31][32][33][34] …”
Section: Discussionmentioning
confidence: 99%
“…An excellent example would be the development of a model of inter-professional education that could enhance care through better collaboration across health disciplines in health care settings. [30][31][32][33][34] …”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals who are successfully practicing IPC are therefore presenting patients with an image of a united group of experts doing all they can to help. Studies have shown that interprofessional education (IPE) regarding IPC is a way to address "health care issues such as efficiency and patient safety", while also improving patient outcomes, communication skills, and job satisfaction of both SPTs and practicing physical therapists [5].…”
mentioning
confidence: 99%
“…One study has suggested that to implement IPC effectively as a healthcare professional, there needs to be an emphasis on IPE in the academic setting as well as clinical IPE that is guided by the clinical instructor (CI) [5]. In the United States, IPE is becoming more of a point of focus within physical therapy programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IPL projects which have been established within existing practice settings are highly varied -student participation in IP seminars whilst on placement; students modelling IP teams to solve problems; students visiting or working with service users and families. 16,[21][22][23][24] Since initiatives are designed to suit local working practices and opportunities, variability is to be expected; however it creates difficulty in establishing relative effectiveness and generalisability of different initiatives, which argues the need for further evaluative research. 13 Practice-based IPL offers excellent opportunities to engage service users in educational initiatives.…”
Section: Introductionmentioning
confidence: 99%